2019
DOI: 10.1002/cptc.201900038
|View full text |Cite
|
Sign up to set email alerts
|

Successive Photoswitching and Derivatization Effects in Photochromic Dithienylethene‐Based Coordination Cages

Abstract: A new series of [Pd2(L)4] cages based on photochromic dithienylethene (DTE) ligands allowed us to gain insight into the successive photoswitching of multiple DTE moieties in a confined metallo‐supramolecular assembly. Three new X‐ray structures of [Pd2(o‐L4)4], [Pd2(o‐L1)2(c‐L1)2] and [Pd2(c‐L1)4] (o‐L and c‐L = open and closed forms of DTE ligands, respectively) were obtained. The structures deliver snapshots of three different combinations of DTE photoisomeric states within the cage, facilitating a compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 99 publications
0
29
0
4
Order By: Relevance
“…[31] Although thesee xamples nicelys howed the preparation of covalently linked molecular architectures,t hose capable of contraction and expansion of their structures by externals timuli or speciesc oncomitant with switching of molecular recognition capabilities remain less explored. [32,33] Recently,w edemonstrated that substituents on the 6'-positions of 2,2'-bipyridyl arms on the wide rim of resorcinarenebasedc apsules regulate the size of the inner cavity; [34] a p-methoxyphenyl-substituted capsule expanded the cavityb ya pproximately 2 compared with its methyl-substitutedc ounterpart. This expansion is caused by interactions between the electron-rich p-methoxyphenyl group and the electron-deficient bipyridyl arm distortingthe coordination environments of the four metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Although thesee xamples nicelys howed the preparation of covalently linked molecular architectures,t hose capable of contraction and expansion of their structures by externals timuli or speciesc oncomitant with switching of molecular recognition capabilities remain less explored. [32,33] Recently,w edemonstrated that substituents on the 6'-positions of 2,2'-bipyridyl arms on the wide rim of resorcinarenebasedc apsules regulate the size of the inner cavity; [34] a p-methoxyphenyl-substituted capsule expanded the cavityb ya pproximately 2 compared with its methyl-substitutedc ounterpart. This expansion is caused by interactions between the electron-rich p-methoxyphenyl group and the electron-deficient bipyridyl arm distortingthe coordination environments of the four metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…This cage consisted of two square‐planar‐coordinated Pd II ions and four ligands with a photochromic dithienylethene ( DTE ) backbone. Recently, they demonstrated that the different external substituents modified on the ligands did not change neither the assembly of the cage nor the photoswitching characteristics [29] . What is more, they exhibited the temporal relationship between the stepwise photocyclization events and guest release of the photoresponsive cage with four DTE photoswitches [30] .…”
Section: Photoresponsive Host‐guest Systemsmentioning
confidence: 99%
“…Recently, they demonstrated that the different external substituents modified on the ligands did not change neither the assembly of the cage nor the photoswitching characteristics. [29] What is more, they exhibited the temporal relationship between the stepwise photocyclization events and guest release of the photoresponsive cage with four DTE photoswitches. [30] It was found that cyclization of the first DTE is enough to expel the guest from the cavity of cage.…”
Section: Photoresponsive Hostsmentioning
confidence: 99%
“…For this purpose, various organics, organometallics, and metal-organic supramolecular or hybrid systems have been designed, including some wonderful work such as the light-switchable coordination cages reported by Clever and so on. [42][43][44] In these studies, the formation and photoswitching behaviour of metal-organic cages have been reported to incorporate similar dithienylethene moieties. However, to the best of our knowledge, the integration of multiple lightswitchable DTE components into well-dened organic cages has less been explored.…”
Section: Introductionmentioning
confidence: 99%